Maya E Groups : Calendars, Astronomy, and Urbanism in the Early Lowlands - Murdock, Jerry; Dowd, Anne S.; Chase, Arlen F. (Arlen Frank), 1953-; Freidel, David A. (Book collections on Project MUSE., 2017)
"E groups" are not the fifth element but a group of structures in the temple complexes of Classic Maya City centers. In this volume from distinguished researchers of the Classic period, the E groups prove to be more than just records of the sun's passages through the years.